The dynamic evaporation process of the deep eutectic solvent LiTf2N:N-methylacetamide at ambient temperature. Issue 22 (22nd May 2019) - Chen, Yu; Yu, Dongkun; Fu, Li; Wang, Meng; Feng, Dongran; Yang, Yingze; Xue, Xiaomeng; Wang, Jinfang; Mu, Tiancheng
Abstract : The dynamic evaporation process of the lithium-based deep eutectic solvent LiTf2 N:NMA under ambient conditions can be divided into three stages. Abstract : Lithium-based deep eutectic solvents (DESs) are potential and promising electrolytes for energy-storing devices such as the lithium-ion battery and supercapacitor due to their greenness, low cost, favorable stability, and ease of synthesis. LiTf2 N (lithium bis(trifluoromethylsulfonyl)imide):NMA ( N -methylacetamide) is a liquid due to the strong intermolecular H-bonding interaction between the H-bonding acceptor (HBA, LiTf2 N) and H-bonding donor (HBD, NMA). The properties (melting point, conductivity, viscosity, etc. ) of LiTf2 N:NMA change with the evaporation of NMA from LiTf2 N:NMA, which would further influence the performance of the energy-storing devices. The evaporation of DES should be determined by the intermolecular interactions. Here, for the first time, the dynamic process of evaporation and intermolecular interactions of the DES LiTf2 N:NMA at room temperature were investigated and we find that the evaporation mechanism of the DES LiTf2 N:NMA can be divided into three stages. In the first stage (before 110 min), the H-bonding interaction between O in LiTf2 N and NH in NMA is disrupted before destruction of the coordinating interaction related to amide II CO and Li cation. In the second stage (from 110 min to 270 min), the change of coordinating interaction related to amide II CO and Li cation is also higher than that of the H-bonded interaction. In the third stage (after 270 min), evaporation of NMA from LiTf2 N:NMA has very little influence on the environment of LiTf2 N:NMA. This work provides a guide for designing DESs as electrolytes for energy-storing devices such as the lithium-ion battery and supercapacitor.